Pleistocene Mollusca of the Colon Deposit, St. Joseph County, Michigan - Clyde Francis Wootton (Hello World!, 1975)
A study was made of a Pleistocene marl deposit in Michigan. Emphasis was placed on a quantitative study of the Mollusca which could be identified from the calcareous mud. The purpose was to reconstruct the paleoecology of the deposit using the ecologic factors provided by the mollusks.